2005
DOI: 10.1111/j.1551-2916.2005.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Spray‐Pyrolysis Technique to Produce Nanocrystalline Lanthanum Strontium Manganite Powder

Abstract: Nanocrystalline, single phase, and highly homogeneous La0.84Sr0.16MnO3 (LSM) powder was prepared by a unique spray‐pyrolysis process for solid oxide fuel cell applications. Atomization of a citrate–nitrate precursor solution consisting of La3+, Sr2+, and Mn2+ ions in the molar ratio 0.84:0.16:1.0, which can initiate a controlled exothermic anionic oxidation‐reduction reaction leading to a self‐propagating auto‐ignition (self‐ignition) reaction within individual droplets led to the conversion of the precursor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…One method demonstrated to offer tailored microstructures is spray pyrolysis, which deposits thin films with controlled thickness and uniformity through atomisation of a precursor solution producing a film on contact with a heated substrate (250–500 °C). SP has been used to deposit various cathode materials for SOFCs, such as La 0.84 Sr 0.16 MnO 3− δ , 6 La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3− δ 7 and La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3− δ :Ce 0.9 Gd 0.1 O 2− δ composites. 8 V. Zapata-Ramírez et al reported the synthesis of SrFeO 3− δ -based cathodes deposited by spray pyrolysis with enhanced electrode behaviour due to improved homogeneity, distribution, and adhesion at the electrode–electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%
“…One method demonstrated to offer tailored microstructures is spray pyrolysis, which deposits thin films with controlled thickness and uniformity through atomisation of a precursor solution producing a film on contact with a heated substrate (250–500 °C). SP has been used to deposit various cathode materials for SOFCs, such as La 0.84 Sr 0.16 MnO 3− δ , 6 La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3− δ 7 and La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3− δ :Ce 0.9 Gd 0.1 O 2− δ composites. 8 V. Zapata-Ramírez et al reported the synthesis of SrFeO 3− δ -based cathodes deposited by spray pyrolysis with enhanced electrode behaviour due to improved homogeneity, distribution, and adhesion at the electrode–electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%
“…It has the capability of controlling the shape, size, composition and phase homogeneity of the particles due to the easy control of parameters. The extremely large choice of precursors along with simple equipments for mass production of large areas have made spray pyrolysis an industry compatible manufacturing technique for synthesis of porous films with wellcontrolled microstructures [4,19,[21][22][23][24]. The pump conducts the solution to the vaporizer chamber and the precursor solution is atomized to droplets that undergo a pyrolytic decomposition upon hitting a heated substrate [25].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 There are various processing techniques available for the preparation of LSM powders. 2,3,5,7,[9][10][11][12] Recently, the gel-casting technique has been used to prepare cell components of SOFCs such as NiO/SDC composite anode 13,14 and yttria-stabilized zirconia (YSZ) and Ce 0.9 Gd 0.1 O 2 electrolyte powders. 15,16 Gel-casting was first reported by Omatet et al 17 in 1991.…”
Section: Introductionmentioning
confidence: 99%